ASSESSMENT OF HIATAL HERNIA DIAGNOSED IN PATIENTS WITH GASTROESOPHAGEAL REFLUX DISEASE BY ESOPHAGEAL MANOMETRY - Imanli, G.A.; Alikhanova, I.Ch.; Gafarov, I.A. (World of Medicine and Biology, 2023)
The purpose of the study was to assess the diagnostic significance (sensitivity and specificity) of hiatal hernia detected by esophageal manometry in patients with gastroesophageal reflux complaints and in persons who were referred for a “check-up” without complaints. 60 patients with gastroesophageal reflux disease who applied with complaints of gastroesophageal reflux (main group) and 35 patients who applied for the purpose of “check-up” (control group) were included in our study. In 95 patients who underwent esophagogastroduodenoscopy, additional esophageal manometry and 24-hour esophageal impedance pH-metry were performed. The sensitivity for endoscopic hiatal hernia in the diagnosis of hiatal hernia on esophageal manometry was 87.5±5.2 %, and the specificity was 70.9±6.1 %. The sensitivity for the esophagus biopsy was 88.9±10.5 %, and the specificity was 100.0±0.0 %. For integrated relaxation pressure-4sec sensitivity was 62.5±7.7 %, specificity was 75.5±5.9 %. In total statistical analysis revealed 100 % specificity and 88.9 % sensitivity of esophageal manometry in diagnosing hiatal hernia. Thus, a significant correlation was found between hiatal hernia detected on esophageal manometry and 24-hour esophageal impedance pH-metry. The use of these methods in the diagnosis of hiatal hernia can lead to an increase in the effectiveness of the prevention of pathological conditions associated with hiatal hernia.